2020
DOI: 10.2147/idr.s236326
|View full text |Cite
|
Sign up to set email alerts
|

<p>Analysis of the Epidemiological, Clinical Characteristics, Treatment and Prognosis of Human Brucellosis During 2014–2018 in Huludao, China</p>

Abstract: Purpose: To describe the incidence trend, demographic and clinical characteristics, treatment and prognosis, epidemiological history and risk factors of human brucellosis in Huludao, China. Patients and Methods: A total of 1887 brucellosis patients were reported in Huludao, China from January, 2014 to December, 2018 and the case questionnaires from 1149 patients were collected from Huludao Municipal Center for Disease Control and Prevention. Demographic characteristics of the patients and the information relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
12
0
2
Order By: Relevance
“…Tongliao City is one of the highest risk areas for human brucellosis in Inner Mongolia (China), as Tongliao city is geographically close to Hinggan League, incidence rates increased dramatically from 9.2/100 000 in 2007 to 69.2/ 100 000 in 2011, then decreased from 2012 to 2016; incidence rates rose again in 2017 to 44.3/100 000 [25]. The incidence of human brucellosis was high from 2014 to 2018 in Huludao, China, primarily due to contact with domestic animals without sufficient protective measures [26]. Previous investigation results [27] showed that serum samples from 226 human, 669 sheep, and 54 calves were collected from 12 villages in Horqin Youyi Zhongqi and Tuquan Xian in 1987, and no positive samples were detected except one sample from sheep from Horqin Youyi Zhongqi.…”
Section: Discussionmentioning
confidence: 99%
“…Tongliao City is one of the highest risk areas for human brucellosis in Inner Mongolia (China), as Tongliao city is geographically close to Hinggan League, incidence rates increased dramatically from 9.2/100 000 in 2007 to 69.2/ 100 000 in 2011, then decreased from 2012 to 2016; incidence rates rose again in 2017 to 44.3/100 000 [25]. The incidence of human brucellosis was high from 2014 to 2018 in Huludao, China, primarily due to contact with domestic animals without sufficient protective measures [26]. Previous investigation results [27] showed that serum samples from 226 human, 669 sheep, and 54 calves were collected from 12 villages in Horqin Youyi Zhongqi and Tuquan Xian in 1987, and no positive samples were detected except one sample from sheep from Horqin Youyi Zhongqi.…”
Section: Discussionmentioning
confidence: 99%
“…After the outbreak of COVID-19, various prevention and control measures limited population mobility and reduced the import of malaria cases in Jiangsu Province. About the brucellosis, sheep/goat were the main contacted animals [26]. In our study, the incidence of brucellosis in February 2020 decreased, the reason maybe that since the COVID-19 outbreak, restrictions such as lockout and shutdowns may have reduced pastoralists' access to livestock and prevented the spread of brucellosis.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, the 50–59-year-old age group had more cases; the ratio of males to females of 3.40:1 was similar to the results of previous studies 16 , 23 . Another study showed that a total of 1149 human brucellosis data points were collected during 2014–2018 in Huludao (China), with a mean age of 49.59 ± 13.14 years, and 75.7% were male 24 .…”
Section: Discussionmentioning
confidence: 99%